Proyecto De Inversión Para La Exportación De Fajas Luxury Femeninas De Bogotá-Colombia Hacia Los Ángeles, California – Estados Unidos (2023)
Historically, the textile sector has been very important for the Colombian economy, generating employment and contributing to the development of regions such as Antioquia. Said growth has been accompanied by an increase in the number of exports of different types of clothing, including girdles. cifIt is precisely this growth that has led to the development of research aimed at the internationalization of these products, such is the case of authors such as: (Claros, 2008; Sanchez, Botero Hernandez, & Gomez D, 2014; Corrales, 2018).